Peranan Keluarga Dalam Pelaksanaan Pendidikan Agama Islam Di Lingkungan 6 Kelurahan Satria Kecamatan Padang Hilir Kota Tebing Tinggi - Najwansyah, Fahri; Nasution, Herry Syahbannuddin; Syahlan, Ali (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This study aims to determine (1) The form of Islamic religious education instilled by families in children in Neighborhood 6, Satria Village, Padang Hilir District, Tebing Tinggi City (2) The role of families in instilling Islamic religious education in children in Neighborhood 6, Satria Village, Padang Hilir District, Tebing Tinggi City (3) Supporting and inhibiting factors for the role of families in instilling Islamic religious education in children in Neighborhood 6, Satria Village, Padang Hilir District, Tebing Tinggi City. This type of research uses a qualitative-descriptive research method. Data obtained through interview, observation and documentation techniques. The data analysis techniques used are data reduction techniques, data presentation, and data verification/drawing conclusions. The technique for checking the validity of the data is to use persistence/consistency and triangulation. The results of this study indicate that: (1) The form of Islamic religious education instilled by families in children in Environment 6, Satria Village, Padang Hilir District, Tebing Tinggi City is education in faith, worship, morals, and morals (adab) (2) Families, especially parents, act as educators, motivators, supervisors, role models, and providers of learning facilities for children. (3) Supporting factors are the family's economic situation, high parental education, a good community environment, parental determination, and children's enthusiasm for learning. While the inhibiting factors are a less than good environment, technological developments, parents' busyness, parents who do not understand Islamic teachings, children's low intelligence levels, and children's laziness to learn.